Treatment of Hypertension Induces a Fall in Platelet Basal Cytoplasmic Calcium Concentration without Influencing Platelet Aggregation - Wilson, J; Orchard, M A; Prentice, C R M; Lees, A D; Baig, M W; Perrins, E J; Davies, J A (Thrombosis and Haemostasis, 1992)
The relationship between blood pressure and platelet basal cytoplasmic calcium concentration ([Ca2+]i) and platelet sensitivity to aggregating agents in hypertension has been investigated in hypertensive patients and normotensive subjects. Ten severely hypertensive patients whose blood pressures were poorly controlled with metoprolol, were given calcium antagonist (either nifedipine or felodipine) as a second line agent. Venous blood samples were collected at each treatment phase for measurement, in whole blood, of platelet aggregation in response to ADP and collagen, and of basal [Ca2+]i using fura-2. Control of blood pressure by the combination of metroprolol and a calcium antagonist induced a significant decrease in median [Ca2+]i from 116 (76–181) to 73 (60–83) nM, which was similar to the median value of 70 (61–80) nM obtained in 14 normotensive subjects. Overall [Ca2+]i correlated with mean blood pressure (r = 0.51). Treatment of hypertension with calcium antagonist did not change the response of platelets to collagen or ADP. The results confirm that effective treatment of hypertension significantly reduced basal [Ca2+]i in platelets but raise doubts whether elevated basal [Ca2+]i is necessarily the sole mechanism by which the sensitivity of platelets to aggregatory agents is increased in hypertension.